Outcome of patients with acute symptomatic pulmonary embolism and psychiatric disorders. Issue 193 (September 2020) - Velasco, Diurbis; Jiménez, David; Bikdeli, Behnood; Muriel, Alfonso; Marchena, Pablo Javier; Tzoran, Inna; Malý, Radovan; López-Reyes, Raquel; Riera-Mestre, Antoni; Monreal, Manuel; ,
Abstract: Objective: To address the association between psychiatric disorders and short-term outcomes after acute symptomatic pulmonary embolism (PE ). Methods: We identified adults with PE enrolled in the RIETE registry between December 1, 2013, and January 31, 2019. Using multinomial regression, we assessed the association between a history of psychiatric disorders and the outcomes of all-cause mortality, PE-related mortality, and venous thromboembolism recurrence and bleeding rates through 30 days after initiation of treatment. We also examined the impact of depression on all-cause and PE-specific mortality. Results: Among 13, 120 patients diagnosed with acute PE, 16.1% (2115) had psychiatric disorders and 4.2% died within the first 30-days of follow-up. Patients with psychiatric disorders had increased odds for all-cause (adjusted odds ratio [OR ] 1.50; 95% CI, 1.21 to 1.86; P < 0.001) and PE-related mortality (adjusted OR 1.64; 95% CI, 1.09 to 2.48; P = 0.02) compared to those without psychiatric disorders. Multinomial logistic regression showed a non-significant trend toward lower risk of recurrences for patients with psychiatric disorders (adjusted OR 0.49; 95% CI, 0.21 to 1.15; P = 0.10). Psychiatric disorders were not significantly associated with increased odds for major bleeds during follow-up (adjusted OR 1.09; 95% CI, 0.85 to 1.40; P = 0.49). Results were consistent in a sensitivity analysis that only considered patients with a diagnosis of depression. Conclusions: In patients with acute PE, history of psychiatric disorders might predict all-cause and PE-related death in the ensuing month after diagnosis. Highlights: If psychiatric disorders are associated with prognosis after PE, interventions might be worth testing to mitigate outcomes. In patients with PE, history of psychiatric disorders is a predictor of death in the ensuing month after diagnosis. Depression was associated with a 1.4-fold increase in the odds of 30-day all-cause mortality.